Cultural History and Community Solidarity of Falcha in Kirtipur - Maharjan, Reena (Shahid Kirti Multidisciplinary Journal, 2025)
Falchas are public shelters constructed and maintained by the Newar community historically. The primary functions of Falcha were: shelter for visitors/porters from out of valley, mid-day rest and community gathering in the evening. The specific Falcha has specific as well as general cultural importance, social value, and latent functions in Kirtipur. Falcha as easy accessed public social space neighbors used to sit, chat, make community meetings, plans and share the grief and happiness of their family issues. The paper tries to explore cultural and functional importance of Falchas in recent contexts. The additional objective of the article is to explore community solidarity, entertainment, identity and latent function like mental health contributions. I employed qualitative research design to collect stories of changing values and different functions of different Falchas. After few transect walks at the Falchas in Kirtipur, I explore knowledgeable people for specific Falcha. Then, I employed observation and key-informants interview methods to collect information. Being Newar of the Kirtipur, I added my personal reflections and family engagement for the construction, and perpetuation of social life of the Falcha in Kirtipur. Falcha played significant contribution for community solidarity, cultural identity, cultural economy through Falcha tourism. The policy implication of the Falcha can be social and mental health healing of senior citizens through social, cultural and music space in the age of increasing individualism, techno-centrism and crisis of social life.